Severe G6PD deficiency leads to recurrent infections and defects in ROS production: Case report and literature review - Sun, Bijun; Li, Qifan; Dong, Xiaolong; Hou, Jia; Wang, Wenjie; Ying, Wenjing; Hui, Xiaoying; Zhou, Qinhua; Yao, Haili; Sun, Jinqiao; Wang, Xiaochuan (Frontiers in Genetics, 2022)
Purpose: Severe glucose-6-phosphate dehydrogenase (G6PD) deficiency can lead to reduced nicotinamide adenine dinucleotide phosphate oxidase activity in phagocytes, resulting in immunodeficiency, with a limited number of reported cases. Here, we aimed to report a child with severe G6PD deficiency in China and investigate the mechanism of his recurrent infections. Methods: The clinical manifestations and immunological phenotypes of this patient were retrospectively collected. Gene mutation was detected by whole-exome sequencing and confirmed by Sanger sequencing. Dihydrorhodamine (DHR) analysis was performed to measure the respiratory burst of neutrophils. Messenger ribonucleic acid and protein levels were detected in the patient under lipopolysaccharide stimulation by real-time quantitative reverse transcription polymerase chain reaction and Western blot. A review of the literature was performed. Results: A male child with G6PD deficiency presented with recurrent respiratory infections, Epstein‒Barr virus infection and tonsillitis from 8 months of age. Gene testing revealed that the proband had one hemizygous mutation in the G6PD gene (c.496 C>T, p. R166C), inherited from his mother. This mutation might affect hydrophobic binding, and the G6PD enzyme activity of the patient was 0. The stimulation indexes of the neutrophils in the patient and mother were 22 and 37, respectively. Compared with healthy controls, decreased reactive oxygen species (ROS) production was observed in the patient. Activation of nuclear factor kappa-B (NF-κB) signaling was found to be influenced, and the synthesis of tumor necrosis factor alpha (TNF-α) was downregulated in the patient-derived cells. In neutrophils of his mother, 74.71% of the X chromosome carrying the mutated gene was inactivated. By performing a systematic literature review, an additional 15 patients with severe G6PD deficiency and recurrent infections were identified. Four other G6PD gene mutations have been reported, including c.1157T>A, c.180_182del, c.514C>T, and c.953_976del. Conclusion: Severe G6PD deficiency, not only class I but also class II, can contribute to a chronic granulomatous disease-like phenotype. Decreased reactive oxygen species synthesis led to decreased activation of the NF-κB pathway in G6PD-deficient patients. Children with severe G6PD deficiency should be aware of immunodeficiency disease, and the DHR assay is recommended to evaluate neutrophil function for early identification.